Rejecting “Controversial” Issues in Education: A Case Study of Ultra-Orthodox Jewish Schools in Belgium - Franken, Leni (Religions, 2020)
In liberal democracies, fundamental rights and freedoms can conflict, and if they do, it is not always clear which right the state should prioritize. Should the right of parents to choose education in line with their own convictions prevail, or should the right of children to be prepared for a future life in a liberal democratic society be given more moral weight? While the former might lead to establishing and subsidizing orthodox religious schools, the latter implies “liberal”, “autonomy-facilitating” education. In order to make this tension concrete, we focus on a case study of an ultra-orthodox Jewish (Haredi) school in Flanders (Belgium), where “controversial issues” are excluded from the curriculum and where education is not fully in line with the core principles of “liberal education”. Subsequently, we explore the legal educational context in liberal democracies, with a particular focus on the freedom of religion and education. Then, we scrutinize several arguments for or against ultra-orthodox faith-based schools. We conclude that there are no convincing arguments for state support for these kinds of schools and that the recent Flemish policy of homeschooling might be a reasonable alternative, wherein a balance is found between children’s rights and parental rights.